Ketimpangan Transparansi dalam Pengelolaan Pajak: Analisis Prinsip Akuntabilitas dan Transparansi dalam Good Governance - I Kadek Anca Liana; Ida Bagus Putu Cleo Davaputra Gosita (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
Taxes are the main source of state revenue and play a vital role in national development and public welfare. However, their effectiveness is highly influenced by the level of transparency and accountability in their management. This study aims to analyze the implementation of transparency and accountability principles in Indonesia’s taxation system, identify the existing forms of transparency inequality, and assess their implications for the principles of good governance. The research employs a qualitative approach through an analysis of various laws, regulations, and recent studies related to tax management. The findings indicate that transparency inequality still occurs in several aspects, such as limited public access to information, uneven implementation of tax digitalization across regions, and a lack of openness in reporting tax incentives. These conditions directly affect government accountability, public trust, and fairness within the national taxation system. Legally, such inequalities contradict the principles of public information disclosure, the justice principle stated in Article 23A of the 1945 Constitution, and the principle of equality before the law. This study recommends strengthening tax transparency regulations, integrating a national digital taxation system, and increasing public participation in fiscal oversight to establish a fair, accountable, and law-based tax governance framework.